TAFSSA District Agrifood Systems Assessment in Nepal 2023: Market Survey - International Rice Research Institute; International Food Policy Research Institute (International Food Policy Research Institute, 2024)
TAFSSA (Transforming Agrifood Systems in South Asia) is a CGIAR Regional Integrated Initiative aimed at advancing equitable access to sustainable healthy diets, enhancing farmers' livelihoods and resilience, and conserving natural resources such as land, air, and water across South Asia. The TAFSSA district agrifood systems assessment seeks to establish a robust, accessible, and integrated evidence base that connects farm production, market access, dietary patterns, climate risk responses, and natural resource management, with gender considerations integrated throughout. The assessment focuses on rural areas in Bangladesh, India, and Nepal, utilizing a district-level, multi-year approach. Data was collected between February and June 2023 in the Banke and Surkhet districts of Nepal. The survey covered 25 wards in each district, focusing on formal and informal multi-vendor markets offering a variety of food products. The survey utilized pretested, structured questionnaires divided into three distinct modules: 1. Interview-Based Module: Gathered information on vendors, assortments of essential goods, availability, resilience, food sourcing, food wastage, and dimensions of access and protection. 2. Observation + Photo-Based Module: Documented market details, infrastructure, and aspects related to food quality, safety, and hygiene. 3. Food List Module: Recorded the availability and prices of an extensive list of food items found in the markets.